Volatile Fraction Composition of Venezuelan Sweet Orange Essential Oil (Citrus Sinensis (L.) Osbeck) - Ojeda de Rodríguez, Graciela; Ysambertt, Fredy; Sulbarán de Ferrer, Betzabé; Cabrera, Lilibeth (Ciencia)
The volatile fraction composition of Venezuelan sweet orange essential oil obtained by cold-pressed fruit peels was studied in this work by GC and GC-MS. Forty-two components were identified in the oil. The monoterpene limonene was the most abundant component. In the oxygenated fraction, aldehydes were the main components followed by alcohols and esters. Among them, decanal, linalool, and decyl acetate were the most relevants. Sesquiterpene hydrocarbons were found in low quantities